Assessing the potential effect of extreme weather on water quality and disinfection by-product formation using laboratory simulation. (1st March 2020) - Chang, Chia-Jung; Huang, Chin-Pao; Chen, Chia-Yang; Wang, Gen-Shuh
Abstract: Increased frequency and severity of extreme weather events (i.e., floods and droughts) combined with higher temperatures can threaten surface water quality and downstream drinking water production. This study characterized the effects of extreme weather events on dissolved organic matter (DOM) washout from watershed soils and the corresponding contribution to disinfection by-product (DBP) precursors under simulated weather conditions. A laboratory simulation was performed to assess the effects of temperature, drought, rainfall intensity, sea level rise, and acid deposition on the amount of DOM released from soil samples. DBP formation potentials (DBPFPs) were obtained to assess the effect of extreme weather events on DBP formation and drinking water quality. The results demonstrated that the dissolved organic carbon (DOC) and carbonaceous DBP levels increased with increasing temperature in a dry (drought) scenario. Regardless of the watershed from which a soil sample was obtained and the incubation temperature during rewetting or chlorination processes, the DOC and carbonaceous DBP levels also increased with increasing temperature. Brominated DBP formation was increased when bromide was present during the rewetting of soil, indicating the effect of sea level rise. When bromide was present during the chlorination of water for DBPFP tests, only the level of brominated DBPs increased. Acid deposition had various effects under different weather conditions. The results of heavy rainfall simulations suggested that water quality deteriorates at the beginning of an extreme rainfall event. Abundant DOM was washed out of soil, leading to a peak in the DBPFP level. The level of DOM in seepage water was less than that of the surface runoff water during rainfall. The situation was more severe when the rainfall came after a long drought and the drought–rewetting cycle effect occurred. Graphical abstract: Soil samples were incubated at different ambient temperature.DBPFP of the soil organic matter washed out increased with incubation temperature. Image 1 Highlights: Effects of extreme weather events on organic matter washout from soil were assessed. Temperature, bromide, the drought–wetting scenario, and acid deposition were considered. Disinfection by-product (DBP) formation from soil organic matter was measured. Dissolved organic washout and DBP levels increased with increasing ambient temperature. Rainfall simulations showed that water quality deteriorates at the beginning of rainfall events.